2017
DOI: 10.1186/s12906-017-1866-1
|View full text |Cite
|
Sign up to set email alerts
|

Aphrodisiac potentials of the ethanol extract of Aloe barbadensis Mill. root in male Wistar rats

Abstract: Background Aloe barbadensis (AB) is a short stemmed succulent medicinal herb that is being used by locals in Nigeria to enhance libido. Therefore this study evaluates the aphrodisiac potential and acute toxicological effect of A. barbadensis (AB) root in male Wistar rats.MethodsAphrodisiac potential was determined following the oral administration of graded doses (100, 200 and 400 mg/kg) of ethanol extract of A. barbadensis root. Sildenafil citrate (Viagra) and distilled water served as positive and negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
7
35
0
Order By: Relevance
“…Some scientific evidence proves the role of central dopaminergic system in regulating sexual behavior, including sexual desire in humans and animals. Similar results were obtained from other authors' research including [8][9][10][11] etc. To explain this effect of sildenafil, scientists have theorized the effect of sildenafil on the central nervous system, specifically on the central dopaminergic system [12,13].…”
Section: Sexual Desiresupporting
confidence: 91%
“…Some scientific evidence proves the role of central dopaminergic system in regulating sexual behavior, including sexual desire in humans and animals. Similar results were obtained from other authors' research including [8][9][10][11] etc. To explain this effect of sildenafil, scientists have theorized the effect of sildenafil on the central nervous system, specifically on the central dopaminergic system [12,13].…”
Section: Sexual Desiresupporting
confidence: 91%
“…Dates contain alkaloids, saponins and lavonoids which improves aphrodisiac activity (Ali et al, 2013). In case of aloe vera nutritional components such as potassium, calcium, zinc and magnesium and phytochemicals suchphytochemicals such as glycosides, lavonoids and phenols are responsible for improving sexual activity in males (Erhabor and Idu, 2017). Allium cepa contains selenium, copper and zinc whereas Moringa oleifera contains lavonoids, anthraquinone glycosides, tannic acid, carotene and glucose which can be responsible for aphrodisiac activity(activity (Allouh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Animals were tested for mating behavioural study, and serum testosterone determination. The results showed that the mounting frequency and intromission frequency increased on day 1 and day 14and at 100mg/kg dose the testosterone concentration had increased and at 200mg/kg dose a signi icant decrease in testosterone concentration was observed (Erhabor and Idu, 2017).…”
Section: Aloe Barbadensis (Aloevera) (Asphodelaceae) Figure 2: Aloe Bmentioning
confidence: 93%
“…Alkaloids have been reported to increase the dilation of blood vessels in the male sex organ (Zamblé et al, 2008) and are said to be one of the mechanisms of action through which aphrodisiac substances act. The ethanol extract of A. barbadensis was also found to contain an alkaloid, which can be linked to the increased blood flow noticed in the histological studies (Erhabor, 2015). Therefore, phenols, alkaloids and saponins may synergistically or individually be responsible for the aphrodisiac activity of the ethanolic extract of A. barbadensis.…”
Section: Phytochemical and Nutritional Composition Of Ab Rootmentioning
confidence: 87%
“…Investigations into the phytochemical constituents of the ethanol extract and its fractions revealed that glycosides, flavonoids, phenols, tannins and reducing sugars were present in the extract and fractions (Tab 5). The saponin content of the crude extract may have been responsible for the earlier reported aphrodisiac property of A. barbadensis root (Erhabor and Idu, 2017). This is because saponin has been previously postulated as a possible constituent responsible for the aphrodisiac property of Tribulus terrestris.…”
Section: Phytochemical and Nutritional Composition Of Ab Rootmentioning
confidence: 89%